2013
DOI: 10.1242/dev.090993
|View full text |Cite
|
Sign up to set email alerts
|

Specification of hepatopancreas progenitors in zebrafish by hnf1ba and wnt2bb

Abstract: SUMMARYAlthough the liver and ventral pancreas are thought to arise from a common multipotent progenitor pool, it is unclear whether these progenitors of the hepatopancreas system are specified by a common genetic mechanism. Efforts to determine the role of Hnf1b and Wnt signaling in this crucial process have been confounded by a combination of factors, including a narrow time frame for hepatopancreas specification, functional redundancy among Wnt ligands, and pleiotropic defects caused by either severe loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…Zebrafish embryo whole mount ISH was performed as previously described (Lancman et al, 2013). Following ISH, IHC for GFP was carried out as reported with minor modification (Huang et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish embryo whole mount ISH was performed as previously described (Lancman et al, 2013). Following ISH, IHC for GFP was carried out as reported with minor modification (Huang et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Discovering new factors expressed in the developing zebrafish hepatopancreatic system may therefore yield insight into human liver and pancreas development. The monoclonal antibody (mAb) 2F11 is widely used to mark the developing and adult zebrafish hepatopancreatic ducts (HPDs), as well as enteroendocrine cells (Crosnier et al, 2005; Curado et al, 2010; Delous et al, 2012; Dong et al, 2007; EauClaire et al, 2012; Lancman et al, 2013; Manfroid et al, 2012; Matthews et al, 2011; Ninov et al, 2012). Particularly, 2F11 marks the intestinal secretory cells, extra-HPDs (common bile duct, cystic duct, hepatopancreas ampulla, extra-hepatic duct and extra-pancreatic duct), gallbladder, intra-pancreatic (Dong et al, 2007), and intra-hepatic ducts (Lorent et al, 2010; Matthews et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies have shown that Sox32 is required for eventual liver formation in wnt2bb mutant embryos[20]. Recent insights have revealed that other factors such as EpCam and hnf1ba genetically interact with wnt2bb to specify hepatopancreatic progenitors[21,22]. We recently used apc mutant and wnt8- inducible transgenic zebrafish to discover that liver formation required dynamic regulation of the Wnt pathway, with suppression of Wnt activity in early somitogenesis followed by elevated Wnt signaling during the hepatic specification phase[23].…”
Section: Introductionmentioning
confidence: 99%
“…For all experiments, 0.5-1.0nl of plasmid was injected at the 1-cell stage to deliver the following amounts of plasmid DNA: hsp:H2B::mCherry-P2A-sox32 and hsp:mCherryCAAX-P2A-Oct4 (20ng) hsp:Oct4-P2A-mCherry-sox32: (30-35ng) hsp:mCherry: (30ng) mylpfa:Oct4-P2A-mCherry-sox32:(30-35ng) mylpfa:mCherry: (30ng) Antibody Staining: Antibody staining was performed as previously described 43 using the following antibodies and staining reagents: (see Supplement Materials and Methods). Samples were imaged on a Zeiss LSM710 running Zen 2010 (Black).…”
Section: Transient Injections and Heat Shockmentioning
confidence: 99%